Empowering excellence: transforming GIRFT accessibility through a centralised Trust intranet portal: Northern Care Alliance Experience - Ayesha Lala; Robert Nipah; Alistair Craig; Molly Gollop; Shirley Naylor; William Keith Gray; Janet Cox; Katrein Savage; Paul Mcmullen; Alshymaa Eltahan (Future Healthcare Journal)
Background: The Getting It Right First Time (GIRFT) programme is a national initiative focused on enhancing clinical quality and efficiency by minimising unwarranted variations in care.1 Within the Northern Care Alliance (NCA) Trust, we identified that streamlined access to GIRFT-related resources is essential for successful implementation. To support this, a dedicated GIRFT intranet webpage was developed and integrated within the Trust’s broader Service Improvement page, which also hosts the Further Faster programme, quality improvement projects (QIPs), clinical audit and educational resources. Objective: The primary goal was to establish a centralised GIRFT intranet webpage to enhance communication, promote engagement and facilitate structured access to GIRFT resources among clinical and managerial staff. Methods: A QIP drivers diagram was employed to identify six key drivers and corresponding interventions essential for developing the webpage (Fig 1). This initiative was a collaborative effort involving resident doctors within the Trust, the GIRFT Academy, Trust information technology (IT), service improvement, clinical audit, and QIP teams. A comprehensive mailing list comprising 210 addresses of clinical directors and managers from various specialties, including medical, surgical, community, diagnostic and pharmacy sectors, was established to ensure robust engagement.The intranet webpage was designed with clear sections, including:• Overview of GIRFT• Further Faster Programme• Model health system portal• Clinical audit and QIP resources• Clinical specialties• Training and teaching sessionsA centralised GIRFT mailbox was created for feedback and inquiries, with contact details readily accessible on the webpage. Additionally, an introductory section for the GIRFT Fellowship was developed, offering information for prospective candidates, including announcements of upcoming posts and progress reports from current fellows as models for future participants. Results: This is a descriptive abstract for the project overview; formal results will be reported in the full manuscript, including user feedback on the webpage structure, key features and preliminary engagement metrics. Conclusion: The centralised GIRFT intranet webpage stands as a transformative tool for embedding best practices across the Trust. Its development and ongoing refinement, guided by user feedback and audits, will continue to enhance engagement and effectiveness. Crucially, this project redefines the role of resident doctors in service improvement. By shifting their focus from traditional clinical audits to a systems-based, non-clinical initiative, residents are empowered to leverage their skills in communication, collaboration and strategic thinking. This innovative approach showcases their capacity to drive meaningful change at an organisational level, enhancing both their professional growth and the quality of care delivered within the Trust.